Temporal changes in home advantage in English football since the Second World War: What explains improved away performance? - Jacklin, P. B. (Journal of Sports Sciences, 2005)
This study examined temporal trends in home advantage in the top two English football divisions and used change point analysis to test the hypothesis that home advantage has not remained constant over time. Regression analysis was used to model the impact of substitutions (a proxy for "information transfer") and the points system on home advantage. The results suggest that changing from two points for a win to three points for a win has led to a 0.39 reduction (95% confidence interval = 0.21 to 0.56) in the ratio of home wins to away wins. Increasing the number of substitutions is associated with a small increase in the ratio of home wins to away wins, although this is not statistically significant. The evidence indicates that, in this particular context, the extent of home advantage has diminished. This contradicts most other published work, which suggests that home advantage is stable over time. I argue that this reduction is more likely to be the result of the introduction of three points for a win, which has lessened the incentives for away teams to settle for a draw, than an increase in "information transfer". Research into temporal trends in home advantage is interesting in its own right but might, in addition, shed light on determinants of the home advantage phenomenon.